2019
DOI: 10.20944/preprints201910.0142.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aquatic Macrophytes are Seasonally Important Dietary Resources for Moose

Abstract: Moose (Alces alces) are generalist herbivores but are important aquatic-terrestrial ecotone specialists. Aquatic macrophytes are a high-quality food source for moose during the summer, however their relative importance to moose diet is difficult to study. We used stable isotope analysis of carbon and nitrogen from moose hooves and forage (terrestrial plants, aquatic macrophytes, and arboreal lichen) to estimate the diet of moose at Isle Royale National Park, Michigan, USA, and to evaluate the isotopic variabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Similarly, studies of serially sampled moose hooves found higher δ 15 N in layers grown during the summer, related to increased consumption of aquatic plants (see Fig. 2) (Kielland 2001; Tischler et al 2019). This is consistent with the pattern observed here for the undated moose antler (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, studies of serially sampled moose hooves found higher δ 15 N in layers grown during the summer, related to increased consumption of aquatic plants (see Fig. 2) (Kielland 2001; Tischler et al 2019). This is consistent with the pattern observed here for the undated moose antler (Fig.…”
Section: Discussionmentioning
confidence: 79%